2015
DOI: 10.1186/s12937-015-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Nutrition Pathway for Acute Care (INPAC): Building consensus with a modified Delphi

Abstract: BackgroundMalnutrition is commonly underdiagnosed and undertreated in acute care patients. Implementation of current pathways of care is limited, potentially as a result of the perception that they are not feasible with current resources. There is a need for a pathway based on expert consensus, best practice and evidence that addresses this crisis in acute care, while still being feasible for implementation.MethodsA modified Delphi was used to develop consensus on a new pathway. Extant literature and other res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 35 publications
1
111
0
Order By: Relevance
“…Multi-methods are used to address the various research questions and a mixed methods approach Fig. 1 The Integrated Nutrition Pathway for Acute Care [37] with a triangulation design using the convergent model [56] is used to explicitly merge qualitative and quantitative data that will describe how implementation varies by context of hospital site.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-methods are used to address the various research questions and a mixed methods approach Fig. 1 The Integrated Nutrition Pathway for Acute Care [37] with a triangulation design using the convergent model [56] is used to explicitly merge qualitative and quantitative data that will describe how implementation varies by context of hospital site.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, that this work was initiated with a prevalence study defining the problem [3,6,7], which resulted in the development of a knowledge translation product (i.e. INPAC) to overcome the problem [37]. M2E is essentially the action process of the KTA theory and specifically includes the following steps: adapting knowledge to the local context; assessing barriers to knowledge use; selecting, tailoring and implementing interventions; monitoring knowledge use; evaluating outcomes; and sustaining knowledge use.…”
Section: Theoretical Foundation and Framework Used To Guide M2ementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the ongoing high prevalence of malnutrition and the pursuit of patient centered care, there is growing focus on the need to build awareness to make improvements and change the culture of nutrition care in hospital [8,9,19,24]. Currently, prevalence rates at admission remain high and research has shown that the lack of a systematic approach to nutrition care in hospitals may exacerbate the issue [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by the Canadian Malnutrition Task Force found that 45% of patients on medical or surgical wards who stayed more than 2 days were malnourished on admission [3]. Malnutrition often goes undetected [9], which is concerning as it increases mortality, length of stay, and risk of re-admission, even when considering other important covariates such as age, sex, socioeconomic and diseaserelated characteristics [3,[10][11][12][13][14][15]. Malnutrition also increases hospital costs [5,16,17] and in Canada, this is by approximately $2000CDN per malnourished patient when compared to a well nourished patient [18].…”
Section: Introductionmentioning
confidence: 99%